Iso-propyl stilbene: a life cycle signal?. Issue 5 (18th March 2019) - Hapeshi, Alexia; Benarroch, Jonatan Mimon; Clarke, David James; Waterfield, Nicholas Robin
Abstract : Members of the Gram-negative bacterial genus Photorhabdus are all highly insect pathogenic and exist in an obligate symbiosis with the entomopathogenic nematode worm Heterorhabditis . All members of the genus produce the small-molecule 3, 5-dihydroxy-4-isopropyl- trans -stilbene (IPS) as part of their secondary metabolism. IPS is a multi-potent compound that has antimicrobial, antifungal, immunomodulatory and anti-cancer activities and also plays an important role in symbiosis with the nematode. In this study we have examined the response of Photorhabdus itself to exogenous ectopic addition of IPS at physiologically relevant concentrations. We observed that the bacteria had a measureable phenotypic response, which included a decrease in bioluminescence and pigment production. This was reflected in changes in its transcriptomic response, in which we reveal a reduction in transcript levels of genes relating to many fundamental cellular processes, such as translation and oxidative phosphorylation. Our observations suggest that IPS plays an important role in the biology of Photorhabdus bacteria, fulfilling roles in quorum sensing, antibiotic-competition advantage and maintenance of the symbiotic developmental cycle.